Immunohistochemistry study of the effect of Oxalis corniculata extract on 1-methyl- 4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced in mice - K. Aruna,; Devi Raja Rajeswari P, (The Bioscan, 2026)
Growth Immunohistochemistry (IHC) is a laboratory technique used to visualize and study the distribution of specific proteins or antigens within cells and tissues. Neuroinflammation is a hallmark of various neurological disorders. IHC enables researchers to study the distribution and activation of immune cells within the CNS, providing valuable insights into the mechanisms of neuroinflammation. Immune cells play a crucial role in the pathogenesis of neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease. The present study was performed to verify the protective effect of the herb O. corniculata extract on brain, liver and kidney tissues in MPTP treated mice immunohistochemically. Sohxlet extraction method was used to obtain O. corniculata ethanol extract. Histopathological changes and immunohistochemical expression in the peripheral sciatic nerve and cerebral cortex were evaluated. Six groups (I – VI) of mice were used with six mice per group. MPTP treatment elevated the stress indicators, pro-inflammatory cytokines, and apoptotic proteins. Keywords Cresyl violet staining, Crude extract, Histology, Herbal drug, Neuroprotective, Parkinson's disease.